2021
DOI: 10.3390/ijms22147703
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells for Early Ischemic Stroke

Abstract: Clinical treatments for ischemic stroke are limited. Neural stem cell (NSC) transplantation can be a promising therapy. Clinically, ischemia and subsequent reperfusion lead to extensive neurovascular injury that involves inflammation, disruption of the blood-brain barrier, and brain cell death. NSCs exhibit multiple potentially therapeutic actions against neurovascular injury. Currently, tissue plasminogen activator (tPA) is the only FDA-approved clot-dissolving agent. While tPA’s thrombolytic role within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 271 publications
(378 reference statements)
0
12
0
Order By: Relevance
“…In recent years, NSCs have yielded high hopes for the treatment of stroke, especially ischemic cerebrovascular disease [ 6 ]. Theoretically, NSCs transplanted into the penumbra at the edge of cerebral infarction will proliferate for a few generations and then differentiate to supplement neurons and glial cells, thereby repairing damage and improving nerve function.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, NSCs have yielded high hopes for the treatment of stroke, especially ischemic cerebrovascular disease [ 6 ]. Theoretically, NSCs transplanted into the penumbra at the edge of cerebral infarction will proliferate for a few generations and then differentiate to supplement neurons and glial cells, thereby repairing damage and improving nerve function.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the reservation of the cerebral cortex was much better compared to that in the control group only in the group receiving transplantation on day 1 [ 24 ]. Although the origins of stem cells varied, their results indicated that stem cell transplantation in the acute phase of stroke can reduce neurological deficits and improve functional recovery [ 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In fact, although some cerebral ischemia patients really survived, they struggled with the impasse of chronic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are abundant sources of NSCs, as NSCs can be directly obtained from neural tissue or generated from the differentiation of embryonic stem cells or induced pluripotent stem cells. Moreover, NSCs have a strong potential for neuronal phenotypic differentiation, chemotaxis, and migration in vivo and in vitro [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%